An analysis of NREGA: A case study of Punjab (district Mohali) - Gupta, Namita (2010)
The problem of unemployment has become a universal malady and no country, developed or developing, is free from it. Both rural and urban areas are afflicted alike; rather their problems are intertwined as many rural unemployed move to towns in search of a job and contribute to the number of their kind over there. Although Punjab is relatively one of the most progressive and prosperous states of India, it is facing an alarming situation of unemployment. A sizable proportion of the agricultural population is being rendered surplus due to the declining size of the landholdings consequent upon rapid growth of population. Mahatma Gandhi National Rural Employment Guarantee Scheme fosters conditions for inclusive growth ranging from basic wage security and recharging rural economy to a transformative empowerment process of democracy. It is considered a historic initiative assuring employment to the rural households through the processes of a rights-based law. This article seeks to analyse the effectiveness of the Act in District Mohali in Punjab. - Reproduced.
Keywords: Employment - India - Punjab; Employment